2014
DOI: 10.5999/aps.2014.41.6.716
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm to Guide Recipient Vessel Selection in Cases of Free Functional Muscle Transfer for Facial Reanimation

Abstract: BackgroundThe aim of this study was to review the recipient vessels used in our cases of facial reanimation with free functional muscle transfer and to identify patient variables that may predict when the facial vessels are absent. From this we present a protocol for vessel selection in cases when the facial artery and/or vein are absent.MethodsPatients were identified from November 2006 to October 2013. Data was collected on patient demographics, facial palsy aetiology, history of previous facial surgery/trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Though optimal recipient vessel selection is crucial for any free-flap reconstruction, [18][19][20][21][22][23][24] this topic has been neglected in most phalloplasty reports, 25 which only describe the FA and GSV as recipient vessels. 8,10,11,15,[26][27][28][29][30][31] In one of the only available studies discussing alternative recipient vessel choices, 25,39 Danker et al 25 discuss the DIEV's reliability as an adjunct to the GSV for venous outflow, with improvement of outcomes after adding the DIEV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though optimal recipient vessel selection is crucial for any free-flap reconstruction, [18][19][20][21][22][23][24] this topic has been neglected in most phalloplasty reports, 25 which only describe the FA and GSV as recipient vessels. 8,10,11,15,[26][27][28][29][30][31] In one of the only available studies discussing alternative recipient vessel choices, 25,39 Danker et al 25 discuss the DIEV's reliability as an adjunct to the GSV for venous outflow, with improvement of outcomes after adding the DIEV.…”
Section: Discussionmentioning
confidence: 99%
“…Proper recipient vessel selection is crucial for all free flaps, [18][19][20][21][22][23][24] but literature explaining phalloplasty recipient vessel selection is extremely limited. 25 Most phalloplasty descriptions 8,10,11,15,[26][27][28][29][30][31] highlight the femoral artery (FA) and great saphenous vein (GSV) as recipi-When alternatives to the FA, including the deep inferior epigastric artery and its venae comitantes (DIEA/V), are mentioned, only cursory attention is paid to technique and selection rationale.…”
Section: Introductionmentioning
confidence: 99%
“…Although most candidates for facial motion restoration have recipient vessels in the proximity of the paralyzed side of the face, 4,32,33 it is important to state that in radical resection for ablative surgery, and/ or intra-arterial chemotherapy, suitable vessels for microvascular anastomosis might not be available. 34 Some authors 4 recommend abandoning the procedure if no recipient vessels are found in the ipsilateral face or neck. However, we believe that contralateral vessels could be useful to provide blood flow, requiring interposition grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Although not well reported, use of the submental vessel is not new. In a review by Henry et al, among 98 hemifaces that underwent free muscle transfer (not limited to gracilis), 88 used the facial artery for anastomosis and 1 used the “submandibular branch of the facial artery.” Additionally, the review noted that 33% of patients with prior facial surgery or trauma lacked a suitable facial artery.…”
Section: Discussionmentioning
confidence: 99%